Public Debt and Social Expenditure: Friends or Foes? - Eduardo Lora; Mauricio Olivera (Inter-American Development Bank, Research Department, 2006)
This paper assesses the effects of total public debt (external and domestic) on social expenditure worldwide and in Latin America using an unbalanced panel of around 50 countries for the period 1985-2003. The most robust and important finding is that higher debt ratios do reduce social expenditures, as popular opinion holds. This effect comes mostly from the stock of debt and not from debt service payments, indicating that debt displaces social expenditures not so much because it raises the debt burden, but because it reduces the room (or the appetite) for further indebtedness. Loans from multilateral organizations like the World Bank or the Inter-American Development Bank do not seem to ameliorate the adverse consequences of debt on social expenditures. In accordance with popular wisdom, our results indicate that defaulting on debt obligations does help to increase social expenditures. Nonetheless, Latin America is different in some respects. The adverse effects of debt and debt-interest payments are significantly stronger in the region, which makes defaults more beneficial to social expenditures. While many of these conclusions are very heterodox, their main policy implication is not; there is no better way to protect social expenditures than to avoid overindebtedness, especially in Latin America.
Keywords: 330; Öffentliche Schulden; Öffentliche Sozialausgaben; Vergleich; Lateinamerika; Welt